Household wellbeing in rural Papua New Guinea: Analysis from the 2023 PNG Rural Household Survey - Mahrt, Kristi; Schmidt, Emily; Fang, Peixun; Mukerjee, Rishabh (International Food Policy Research Institute, 2025)
Key Messages  The PNG 2023 Rural Household Survey collected detailed consumption and expenditure data, which allows the first cost of basic needs poverty assessment since the 2009/10 Household Income Expenditure Survey. However, it is important to note that the survey is not nationally representative.  43% of sample individuals are estimated to be poor relative to the standard cost of basic needs poverty lines (poor is defined as those who live in households that do not have sufficient resources to acquire calorie adequate diets while also meeting basic non-food needs).  64% of sample individuals are estimated to be poor relative to the healthy diet poverty lines (poor is defined as those who live in households that do not have sufficient resources to meet healthy dietary guidelines while also meeting basic non-food needs).  The healthy diet poverty line incorporates a higher share of nutrient dense food groups (vegetables, fruits, meat and fish, etc.) and thus is about 1/3 more costly than the standard poverty line.  On average, households within the survey sample over-consume staples and fats compared to healthy guidelines and under-consume vegetables, fruits, animal source foods, and nuts/pulses.  Smaller households and households with greater production assets (land and labor), education completion, market access, and income diversification (via non-farm businesses and migrant remittances) are associated with higher household consumption-expenditure (income proxy).  Among households engaged in cash crop sales (i.e., cocoa, coffee, betelnut, horticulture) only cocoa farming households have significantly higher consumption-expenditure (income proxy).  Targeted safety net and community asset building programs could reduce rural poverty by increasing agriculture productivity, supporting rural-urban market linkages, improving demand for rural goods, and incentivizing off-farm employment.  Facilitating remittance transfers from migrants to rural households and facilitating access to primary education could improve rural incomes in the short and long term, respectively.